ANALISIS PERBEDAAN KECERDASAN EMOSIONAL SISWA LAKI-LAKI DAN PEREMPUAN - Musnizar Safari (Universitas Serambi Mekkah, 2019)
Emotional intelligence is one’s ability to manage emotional life with intellegence, keeping emotional harmony and expressing by skill of self introduction, self control, self motivation, empathy and social skills. The student of junior high school are on vulnerable age stage cause a teenager or a dozen years old are in unstable conditions in process during the transition period towards adulthood. Therefore, then needed an ability to manage his emotion well, in order to pas his adolescence well. Analysis of emotional intelligence differences in this male student and female student is aiming to know factors which influence the student emotional intelligence of class VIII Junior High School Inshafuddin, the reason is previous research results by the author self, found that the emotional intelligence level of female is 62,96% is lower 15,42% compared to male student who are emotional intelligence level is 78,38%. Approach taken is descriptive qualitative approach by conducting interviews in data collection. The interview result found that low emotional intelligence of female student influenced by an immature development process; lake of female caregiver who accompany student in dormitory; young age and lake of caregiver understanding about psychological condition of adolescent student especially female student.